Predictive Approach for Power Quality Improvement Based Direct Power Control - Houssam Eddine Medouce; Hocine Benalla (Institute of Advanced Engineering and Science, 2018)
The extensive use of non-linear loads in industry becomes increasingly a serious problem that affects the quality of energy delivered to customers. Therefore, the shunt active power filter (SAPF) has emerged as an important industrial tool to eliminate induced harmonic currents and compensating of reactive power. This paper proposes an improved control configuration for SAPF based on a modern technique called predictive direct power control (Predictive-DPC). The principle of this control is based on the direct regulation of the instantaneous active and reactive powers to guarantee a good energy quality on the grid side. For this purpose the appropriate average voltage vector which cancels power tracking errors is calculated by a simple predictive model at the bigining of each control period. This type of control includes various features such as the lack of look up table (LUTs) and closed current loops and the constant switching frequency is achieved through the use of PWM modulation. The results of the simulation process show a high performance in the steady and transient state function for predictive-DPC control that might be a reasonable alternative to conventional DPC in the field of active power filtering.